When a Right Goes Wrong: The Unintended Consequences of India's Right to Education Act. (18th October 2018) - Iyer, Gopalkrishnan; Counihan, Chris
Abstract: Many private schools in India are under threat of closure as a result of the Right to Education Act 2009 (RTE Act). The Act mandates several input requirements rather than concentrating on learning outcomes. We show that some states are closing private schools despite government schools themselves failing to meet the mandates. We further argue that the RTE Act has the wrong priorities and so has failed to realise its mission of quality education, tends to promote disguised false equity and ignores the secondary education system, which forms an integral part of the formal education system. As a result of this faulty and discriminatory implementation of the law, a statutory 'right' has become a 'wrong'.